Memristor and its applications in logic design and signal processing - Kaushik Anantharaman. (2013)
The three basic circuit elements for building an electronic device are the resistors, the capacitors and the inductors. These circuit elements can be defined by a relation between two of the four fundamental circuit variables: voltage, current, charge and flux. Six possible combinations can be obtained by pairing these four electrical base units. Out of the six possible combinations, five are well defined. In 1971, Chua proposed that there should be a fourth element which defines a relation between flux and charge. He called this element, the memristor, a short for memory resistor.